The role of employees’ empowerment on risk management - Ilhusady, Iman Kassem; Demirel, Yavuz (Center for Strategic Studies in Business and Finance SSBFNET, 2020)
The Libyan economy under the influence of current political risks that is resulted in a sudden halt in petroleum products following the revolution followed by a halt in major economic activities. The banking sector was not immune to these current economic risks therefore, the banking sector faced non-financial and financial risks.  Our study focuses on human resources with a high level of talent and skills and their role to overcome the banking risks faced by the Libyan banking sector. This is of great importance as the first study addressing the empowerment of human resources in effective risk management in the banking sector, especially in Libya. To a chive the objective of the study the questionnaire method was used to collect data, the survey was distributed to 320 employees and six banks operating in the eastern part of Libya were selected as targets to investigate the risks faced by the banking system as a result of the current political crisis. The result of the research demonstrated there is a positive and statistically significant relationship between the dimensions of employees’ empowerment and effective risk management. It was seen that issues such as training, incentives, and participation, sharing of authority, teamwork for employees are important in risk management. In addition, the risk management and strengthening of human resources among the banks in Benghazi and Al Bayda have been found to differ in their dimensions. The findings in this study seem to be consistent with many findings in the literature.
Keywords: 5. Gender equality; 9. Industry and infrastructure; 8. Economic growth; 1. No poverty; 10. No inequality; 16. Peace & justice